Food for Thought: A Comparative Analysis of Eating Behavior in the United States, Poland, and Armenia. (1st October 2016) - Jarosz, Ewa
Abstract: Despite having important consequences for individual health and well-being, daily eating habits are likely to be taken for granted. A comparative perspective helps illustrate eating behaviors specific to a given society. This paper presents an analysis, using nationally representative data, of eating patterns in Armenia, Poland and the United States. There are significant differences between countries in how much time is spent on eating and in the circumstances in which people eat. These differences cannot be explained by labor market or household characteristics. Finally, while countries differ on most analyzed dimensions, in all societies social eating is linked with higher time expenditures.